Math on trial: how numbers get used and abused in the courtroom - Schneps, Leila (Basic Books, 2013)
Math error number 1 : multiplying non-independent probabilities : the Clark case : motherhood under attack -- Math error number 2 : unjustified estimates : the case of Janet Collins : hairstyle probability -- Math error number 3 : trying to get something from nothing : the case of Joe Sneed : absent from the phone book -- Math error number 4 : double experiment : the case of Amanda Knox : media versus justice -- Math error number 5 : the birthday problem : the cold case of Diana Sylvester -- Math error number 6 : Simpson's paradox : the Berkeley sex bias case -- Math error number 7 : "the incredible coincidence" : the case of Lucia de Berk : carer or killer? -- Math error number 8 : underestimation : Charles Ponzi : American dream, American scheme -- Math error number 9 : choosing a wrong model : the case of Hetty Green : a battle of wills -- Math error number 10: mathematical madness : the Dreyfus case : spy or scapegoat?